2011
DOI: 10.1128/aac.01510-09
|View full text |Cite
|
Sign up to set email alerts
|

Multilaboratory Testing of Two-Drug Combinations of Antifungals against Candida albicans , Candida glabrata , and Candida parapsilosis

Abstract: Median ⌺FIC values showed a wide dispersion, and interlaboratory agreements were less than 85% in most instances. Additional studies are needed to improve the interlaboratory reproducibility of antifungal combination testing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 47 publications
3
38
0
Order By: Relevance
“…Each drug alone had very low MIC values for these strains, but they increased following the association, although still remaining low. With regard to echinocandins, most authors found no antagonism between micafungin and azoles or AMB (4,17,32). Barchiesi et al did not find advantages in associating caspofungin and the polyene, with the exception of C. parapsilosis, but the study in- cluded a much more limited number of strains (2).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Each drug alone had very low MIC values for these strains, but they increased following the association, although still remaining low. With regard to echinocandins, most authors found no antagonism between micafungin and azoles or AMB (4,17,32). Barchiesi et al did not find advantages in associating caspofungin and the polyene, with the exception of C. parapsilosis, but the study in- cluded a much more limited number of strains (2).…”
Section: Discussionmentioning
confidence: 86%
“…The evaluation of in vitro drug interactions by FC was determined according to the staining index (SI), which is similar to the FICI described above. The SI was calculated as the sum of the percentage of depolarized cells (DC) after treatment with drug combinations divided by the DC of the drug alone for DiBAC 4 of the checkerboard results, an association provided by FC was defined as antagonism for SI of Ͻ1, no interaction for SI between 1 and 4, and synergy for an SI of Ͼ4.…”
Section: Methodsmentioning
confidence: 99%
“…Regarding the effect of echinocandins on voriconazole inhibition zones when the three echinocandins (at 1, 6, and 12 mg/liter) were combined with voriconazole (at 0.5, 2, and 6 mg/liter) in spiked human serum, there was no difference between the inhibition zones of voriconazole alone and in the presence of each echinocandin (ANOVA P Ͼ 0.18). No interaction between voriconazole and echinocandins against C. parapsilosis isolates has been reported (29)(30)(31).…”
Section: Isolatementioning
confidence: 99%
“…Unfortunately, high costs and serious side effects have put limitation on the combinations of antifungal drugs 12,13 . In addition, contradictory results of the synergistic or antagonistic action of various antifungals combination have been reported 9,14,15 . FLC-like drugs inhibit the cytochrome P450 sterol 14a-demethylase (14DM, CYP51) by coordinating the heme iron atom in the catalytic site with the azole nitrogen atom (N-3 and N-4 in the case of imidazole and triazole respectively).…”
Section: Introductionmentioning
confidence: 99%